2007
DOI: 10.1007/s10709-007-9164-3
|View full text |Cite
|
Sign up to set email alerts
|

‘Good-genes’ and ‘compatible-genes’ effects in an Alpine whitefish and the information content of breeding tubercles over the course of the spawning season

Abstract: Some models of sexual selection predict that individuals vary in their genetic quality and reveal some of this variation in their secondary sexual characteristics. Alpine whitefish (Coregonus sp.) develop breeding tubercles shortly before their spawning season. These tubercles are epidermal structures that are distributed regularly along the body sides of both males and females. There is still much unexplained variation in the size of breeding tubercles within both sexes and with much overlap between the sexes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 55 publications
(6 reference statements)
3
42
0
2
Order By: Relevance
“…In the case of whitefish, the secondary sexual traits are breeding tubercles, i.e., little horny structures (Wiley and Collette 1970). In a previous studies we found that the size of breeding tubercles can sometimes be a significant predictor of offspring survival in whitefish (Wedekind et al 2001(Wedekind et al , 2007a. In roach (Rutilus rutilus), another iteroparous group spawner with external fertilization, the size of breeding tubercles is positively linked to male dominance (Kortet et al 2004a) and male size (Wedekind 1992), but not Table 2 for statistics significantly to sperm velocity (Kortet et al 2004c) nor offspring viability (Kortet et al 2004b).…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…In the case of whitefish, the secondary sexual traits are breeding tubercles, i.e., little horny structures (Wiley and Collette 1970). In a previous studies we found that the size of breeding tubercles can sometimes be a significant predictor of offspring survival in whitefish (Wedekind et al 2001(Wedekind et al , 2007a. In roach (Rutilus rutilus), another iteroparous group spawner with external fertilization, the size of breeding tubercles is positively linked to male dominance (Kortet et al 2004a) and male size (Wedekind 1992), but not Table 2 for statistics significantly to sperm velocity (Kortet et al 2004c) nor offspring viability (Kortet et al 2004b).…”
Section: Discussionmentioning
confidence: 79%
“…They also started the breeding season with larger GSI, i.e., they were able to invest more than younger males into their relative gonad weight (Hellriegel and Blanckenhorn 2002), and their condition factor K was not significantly lower than that of younger males at any time during the spawning season. Recently, Wedekind et al 2007a tested the viability of embryos sired by young and old males of C. zugensis and found no significant negative effect of sire age on offspring viability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As the genetic variability is extremely low in many natural Arctic charr populations [67] inbreeding avoidance can be an important mechanism explaining the evolution of polyandry in the Arctic charr. As it has been demonstrated that good genes and compatible genes may both be involved in female choice at the same time [68-70], these two mechanisms are not mutually exclusive mechanisms of sexual selection.…”
Section: Discussionmentioning
confidence: 99%